Importancia del asesor o comunicador político dentro del proceso electoral de los candidatos a la alcaldía de Montúfar- Carchi- Ecuador, elecciones 2022/ 2023 - Andino Janeta, Kerly Mishell (2023)
This research is based on the need to identify the importance of the political communicator or advisor within the electoral campaigns of the city of San Gabriel, Montúfar canton, province of Carchi, Ecuador. Through the qualitative method where 11 interviews were applied to political communication professionals, former candidates, advisors or communicators. Likewise, the direct observation technique was applied, techniques that contributed to the development of our research. For this purpose, three specific objectives were designed, where the main objective is based on knowing the role of a political communicator or advisor, highlighting the importance of understanding the difference between the role of a communication professional and the work of an empirical person. In addition, it focuses on knowing the scope of disseminating mass messages through social networks and taking care of the candidate's image. This analysis is proposed as a fundamental starting point to understand how advisors or communicators influence the electoral process and how they can effectively contribute to the candidate's success.Similarly, a direct observation was made on Facebook and TikTok platforms where variables.